Atlantoraja cyclophora, Eyespot Skate - Pollom, R. (2020)
The Eyespot Skate (Atlantoraja cyclophora) is a small (to 74 cm total length) skate that occurs in the Southwest Atlantic from Rio de Janeiro, Brazil to San Matías Gulf, Argentina. It inhabits the continental shelf from inshore to 100 m depth, and occasionally to 320 m. It is captured in intensive and largely unmanaged demersal trawl fisheries which operate throughout its geographic and depth range. In southern Brazil there are no time-series of abundance, but fisheries there are intense and it is suspected that they are leading to population reduction. In Uruguay, research trawl catch-per-uniteffort of this species declined 82% from 1,910 kg/hr in 2004–2013 to 343 kg/hr from 2013 to 2017, equivalent to a >95% population reduction scaled over three generations (40.5 years). In the Rio del Plata Estuary, the landings of coastal rays including this species was low until the mid-1990s, but increased retention led to substantial increases in landings which peaked in 2008, followed by a decline. In Argentina, reported landings of skates in general increased from 900 t in 1993 to a peak of 28,000 t in 2007, and then declined to 24,000 t in 2009–2010. Overall, due to intense and increasing fishing pressure across its range, decreasing abundance, and its relatively slow life history, it is suspected that the Eyespot Skate has undergone a population reduction of 50–79% over the past three generations (40.5 years), and it is assessed as Endangered A2bd.